ANALISIS PROFITABILITAS DAN TINGKAT EFISIENSI PADA BANK SYARIAH DI INDONESIA - Kadaria, Rohayati; Palagan, Gilang; Gani, Nur Asni; Permana, Muhammad Fatha (Media Riset Bisnis Ekonomi Sains dan Terapan, 2025)
This study aims to analyse the efficiency level of Islamic banking in Indonesia using an intermediation approach and to analyse bank profitability between Islamic commercial banks from 2015 to 2019. The method used in this study is descriptive analysis, Data Envelopment Analysis (DEA) method. This study found that in the 2015–2019 period, Islamic commercial banks in Indonesia (BRIS, BNIS dan BSM, Bank Muamalat dan Maybank Syariah) in general have not reached a high level of efficiency and there are inefficiencies in the use of inputs and outputs. Third-party funds and labour’s costs affect the financing output. Among those five Islamic commercial banks, the bank obtaining the highest efficiency level, close to 100 points, is BSM, followed by BNIS, then BRIS, BMI, and Maybank. The result of profitability analysis is that the variables NPF, FDR, and inflation simultaneously did not significantly affect the ROA variable.Keywords: efficiency level, profitability, DEA, Islamic commercial bank